Implementasi Penggunaan Media Canva dalam Pembelajaran Kurikulum Merdeka di SMA Pendidikan Keluarga Pematangsiantar - Syahputra, Fikry; Nurlela, Nurlela; Nasution, Vivi Adryani; Nasution, Ely Hayati (TALENTA, 2024)
As one aspect of the Tri Dharma of Higher Education, community service activities are an obligation that must be carried out by every lecturer in higher education. English is a universal language because it is used by most countries in the world as the main language. Apart from that, English is an international language that is important to master or learn. The low use of digital media in independent curriculum learning, especially the use of Canva digital content, is influenced by internal and external factors. This activity aims to see whether the Pematang Siantar Family Education High School teachers can use the Canva application well in making Independent Curriculum teaching materials and whether the teachers are satisfied with the training provided by the Service Team. From the results of the training it can be concluded that the Canva application can help teachers in creating teaching materials based on the Independent Curriculum and almost all teachers (90.9%) who received training in using the Canva application were very satisfied with the material they received.